Hubungan Edukasi Kesehatan dengan Pencegahan Perilaku Merokok Siswa - Nurafriani, Nurafriani; Irwansjah, Nurhasana; Sumi, Susi Sastika; Fajriansi, Andi; Jamaluddin, Maryam (Journal of Telenursing (JOTING), 2024)
This study aimed to determine whether there is a relationship between health education and the prevention of smoking behavior among students at SMA Negeri 11 Makassar. This research method is quantitative and uses a cross-sectional method. The results of this study indicate that the analysis using the chi-square test had a significance level. The statistical test results using chi-square obtained the test results p = 0.001. because the p-value <α = 0.05 means a relationship exists between health education and the prevention of smoking behavior of students at SMA Negeri 11 Makassar. The conclusion is that health education has a significant relationship with efforts to prevent smoking behavior among students. Keywords: Health Education, Smoking Behavior